Optiminization of regeneration at the stages of soft tissue augmentation using a collagen matrix - A. B. Adzhieva; I. A. Voronov; S. S. Ivanov; H. M. Nalchajyan (Эндодонтия Today, 2021)
Lack of adequate width and thickness of periodontal or peri-implant soft tissues can compromise the aesthetics, function or survival of teeth and dental implants. Biomaterials are widely used in dentistry to overcome the disadvantages of autogenous tissue transplantation. The advantage of using biomaterials is that there is no need for re-surgery and that they are available in large quantities. The most widely used biomaterial for soft tissue augmentation is collagen, as it is believed to best mimic the natural cellular environment of the extracellular matrix, although other biomaterials are also candidates for soft tissue regeneration. Collagen matrices differ in composition, three-dimensional structure, elasticity and mechanical stability. Aim. is to review the literature on the optimization of regeneration at the stages of soft tissue augmentation using a collagen matrix.